Good Governance Optimization in The Agricultural Supply Business of Bumdes Latsari - Isnaini Nazil Latus Solikhah; , Omi Pramiana (Proceeding International Conference on Digital Education and Social Science, 2025)
This study analyzes the application of Good Governance principles in the management of the Lestari Makmur Village-Owned Enterprise (BUMDes) Agricultural Drug Store business unit in Latsari Village, with a scope that includes human resource capacity, financial administration, technology utilization, and governance effectiveness. The purpose of the study was to assess the extent to which the principles of transparency, accountability, participation, professionalism, effectiveness, and efficiency are applied in business operations. The method used was descriptive qualitative through interviews with five key informants (Village Head, BUMDes Head, BUMDes Supervisor, Shop Person in Charge, and Farmer Service Users), observation, and documentation. The results of the study indicate that BUMDes management has fulfilled most of the Good Governance principles, demonstrated by manager competence, strong work ethics, implementation of SOPs, information transparency, routine reporting, multi-layered supervision, and community participation in all stages of management. Business effectiveness and efficiency were also achieved through resource optimization and operational innovation, although administrative digitization, stock completeness, and capital strengthening still need to be improved. Overall, BUMDes Lestari Makmur has implemented healthy, transparent, and responsible governance, but improvements in technology and funding aspects are needed to support business sustainability.